2021
DOI: 10.3390/genes12091409
|View full text |Cite
|
Sign up to set email alerts
|

Histone Acetylation Changes in Plant Response to Drought Stress

Abstract: Drought stress causes recurrent damage to a healthy ecosystem because it has major adverse effects on the growth and productivity of plants. However, plants have developed drought avoidance and resilience for survival through many strategies, such as increasing water absorption and conduction, reducing water loss and conversing growth stages. Understanding how plants respond and regulate drought stress would be important for creating and breeding better plants to help maintain a sound ecosystem. Epigenetic mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 88 publications
(158 reference statements)
0
30
0
Order By: Relevance
“…This conclusion is also supported by previous reports in which HDACs play a critical role in regulating abiotic stress responses. For example, histone acetylation changes in plant responses to drought stress [ 35 ]. Arabidopsis HDA6 is required for freezing resistance [ 36 ] and salt stress [ 28 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is also supported by previous reports in which HDACs play a critical role in regulating abiotic stress responses. For example, histone acetylation changes in plant responses to drought stress [ 35 ]. Arabidopsis HDA6 is required for freezing resistance [ 36 ] and salt stress [ 28 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, acetylation of histone is found enriched in several cold-responsive genes ( Park et al, 2018 ). It is regulated dynamically by histone acetyltransferases ( HATs ) and histone deacetylases ( HDACs ) ( Li et al, 2021 ). In recent research, A. thaliana plants were exposed to cold stress, and overexpression of histone deacetylase 2D ( HD2D ) exhibited lower lipid peroxidation with decreased accumulation of malondialdehyde contents that eliminated the oxidative burst ( Han et al, 2016 ).…”
Section: Plant Epigenetic Changes and Regulation During Abiotic Stressesmentioning
confidence: 99%
“…HAT genes TaHAG2 , TaHAG3 , and TaHAC2 were induced under drought stress in a wheat variety called BN207, but not in other varieties with lower drought resistance. Li et al [ 28 ] reported that, in soybean, drought treatment decreased expression levels of nine GmHDAC genes ( GmHDA6 , GmHDA8 , GmHDA13 , GmHDA14 , GmHDA16 , GmSRT2 , GmSRT4 , GmHDT2 , and GmHDT4 ).…”
Section: Acetylationmentioning
confidence: 99%